Spiritual Leadership: Implementation of Leadership Models in Islamic Education Institutions - Yakub, Ali; Patimah, Siti; Hidayatullah, Hidayatullah; Gani, A.; Uyuni, Yuyun Rohmatul (Journal Corner of Education, Linguistics, and Literature, 2025)
This research was conducted to find out about the leadership model and how  implementation of this spiritual leadership model is in Islamic educational institutions. This research uses a qualitative approach with a literature study by examining various sources of literature, both from scientific journals, books, and other literature sources related to spiritual leadership. Based on various sources of literature, the author finds that leadership is very important in an organisation because leadership is a process of influencing others to do their work in accordance with the expected goals. And spiritual leadership is very effective in bringing an organisation to have a conducive climate in the development of an organisation, because spiritual leadership is not only about the intelligence of a leader or the skills of a leader in managing other people and institutions but also upholds the values of honesty, kindness, wisdom, compassion and so on in order to form morals and morals. the application of spiritual leadership in Islamic educational institutions requires the synergy of various aspects: ranging from the quality of leaders, organizational culture, competence and commitment of human resources, to the support of religious facilities and programs. it is hoped that with the results of this study the leaders can apply the spiritual leadership model, especially in Islamic educational institutions.